PEMANFAATAN MEDIA AUDIO VISUAL UNTUK PENGEMBANGAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TK - Emara, Agnes; Ali, Muhammad; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
This research purposes tu describe the utilization of audiovisual media in developing listening skill of children aged 5 to 6 years at Kindergarten. The method of this research is descriptive with qualitative method. The subject of this research was Group B of teachers class at Kindergarten. The techniques to collecting data in this research were observation, interview, and documentation. The results of this research were (1) Planning the utilization of audio visual media, the teacher first prepared the tools and materials to be used such as projector, speaker, laptop, and learning videos according to the learning theme. (2) Implementing the utilization of audio visual media, the teacher displayed a learning video which has been downloaded from Youtube. (3) Evaluate the the utilization of audio visual media, the teacher assessed children worksheets. (4) Some factors inhibited the utilization of audio visual media were the limitations of the media and tools used such as projector and speaker, room lighting was too bright and the lack of teachers